The Strategies Used By English Language Learners To Learn Grammar - Hermansyah, Sam; Sadapotto, Andi; Hambing, Agus; Rambung, Herna (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study sought to identify the various types of learning techniques used by Muhammadiyah Sidenreng Rappang University students enrolled in the English education study program. Seventy-five first-semester students who were enrolled in a basic English grammar course served as the study's subjects. Data collection and analysis were conducted using descriptive quantitative. The study's findings indicated that metacognition (20, 93%), cognitive (18, 49%), social (17, 83%), affective (16, 48%), memory (15, 97%), and compensatory (10, 25%) were the learning strategies that students used the least when studying grammar. Additionally, the ability to focus on a specific grammar pattern, attempt to grasp it, and make connections to previously learned material is another reason why students frequently employ metacognitive strategies when studying grammar. As a result, it is recommended that teachers should be aware of the various learning strategies and then assist the students as they study in order to improve learning outcomes.